ANALYSIS OF MARKET DRIVEN STRATEGIES TO INCREASE CAPABILITIES AND PERFORMANCES ADVANTAGES IN BUSINESS - Deddy Hendarwan (JEES: Journal of Economic Empowerment Strategy, 2023)
Considerable progress has been made in identifying market-driven businesses, understanding what they do, and measuring the bottom-line consequences of their orientation to their markets. The next challenge is to understand how this organizational orientation can be achieved and sustained. Market Orientation is a business culture which enlist the participation of all employee for the purpose of creating superior value for its customers and superior performance for itself. A substantial body of research finds a positive relationship between a business’ magnitude of market orientation and it’s performance. However, there has been no research into the competitive strategies through which a market oriented business creates customer value. This paper extends previous work by showing that market, and attempt to achieve competitive advantage both by increasing customer benefits and by reducing costs. Contrary to traditional reactive market driven approach, the proactive market driving approach pertains to influencing the market structure and the market players behavior in a direction that enhances the company competitive posture. Then companies must be market or customer oriented, think and act based on innovative knowledge, make a useful and long term relationship with their customers. This qualification is for those organizations that are able to be knowledge-based, formulate its marketing strategies and sustain its competitive advantage based on its own knowledge. Companies must consider innovative knowledge as a new input to sustain competitive advantages and to develop intelligent marketing strategy.